Predicting Gen Z Mangrove Conservation Awareness on Instagram: A Community Account Study of Campaign Exposure and Ambassador Credibility in Indonesia - Paundra Hanutama; Sulthan Rafi Abyan Hidayat; Meilannie Louise Hajo; Aditi Jadhav (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
This study measures the role of Instagram as an environmental communication space for Generation Z in Indonesia. Grounded in the frameworks of Environmental Communication and Social Influence Theory, this study positions the variables of community-based digital campaign exposure ("One Man One Mangrove") and youth environmental ambassador credibility as predictors of environmental awareness. A quantitative survey was administered to 96 followers of the Instagram account @mangrovejakarta.id, and the data were analyzed using multiple linear regression. The results show that both exposure to campaign content and perceived ambassador credibility significantly predict environmental awareness (p < 0.05), with ambassadors exerting the strongest standardized relationship (β = 0.704). The two predictors explain 65.4% of the variance in awareness (R² = 0.654), indicating that digitally mediated communication can contribute to the formation of awareness regarding mangrove conservation within this specific follower community. These findings suggest that social media can serve as a potential environmental communication channel for engaging youth audiences in ecosystem-specific issues and may support ongoing efforts to enhance environmental literacy in coastal conservation contexts.